2011
DOI: 10.1007/s10511-011-9195-4
|View full text |Cite
|
Sign up to set email alerts
|

Optical and HI properties of isolated galaxies in the 2MIG catalog. I. General relationships

Abstract: We analyze empirical relationships between the optical, near infrared, and HI characteristics of isolated galaxies from the 2MIG Catalog covering the entire sky. Data on morphological types, K S -, and B-magnitudes, linear diameters, HI masses, and rotational velocities are examined. The regression parameters, dispersions, and correlation coefficients are calculated for pairs of these characteristics. The resulting relationships can be used to test the hierarchical theory of galaxy formation through numerous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…This is in agreement with the results shown in Figure 15, where for log (M * /M ) > 9.5 most galaxies have log (fHI ) < 0. For their higher M * sample Kudrya et al (2011) found a slope (1.00 ± 0.04) in the linear fit of log (MHI /M ) as function of log (M * /M ) which is larger than the slope found here.…”
Section: Scaling Relationscontrasting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with the results shown in Figure 15, where for log (M * /M ) > 9.5 most galaxies have log (fHI ) < 0. For their higher M * sample Kudrya et al (2011) found a slope (1.00 ± 0.04) in the linear fit of log (MHI /M ) as function of log (M * /M ) which is larger than the slope found here.…”
Section: Scaling Relationscontrasting
confidence: 91%
“…However, some of this deviation may be a result of the difference between the M * estimation method used by Huang et al (2012) and the one used here. Kudrya et al (2011) analysed the MHI -to-M * relation for the 2MIG catalogue of isolated galaxies. The galaxies of the 2MIG catalogue have a range of M * higher than that of the EIG sample (with the bulk in the range 7.5 8 8.5 9 9.5 10 10.5 11 11.5 0…”
Section: Scaling Relationsmentioning
confidence: 99%
“…Various optical and hydrogen characteristics of the sample of 2MIG galaxies were considered in [19]. According to the authors [19], the completeness of the catalog is about 80% up to the limiting apparent magnitude of K s = 11.5.…”
Section: Isolated Galaxies Of the 2mig Catalogmentioning
confidence: 99%
“…Various optical and hydrogen characteristics of the sample of 2MIG galaxies were considered in [19]. According to the authors [19], the completeness of the catalog is about 80% up to the limiting apparent magnitude of K s = 11.5. The isolation criterion selects into the 2MIG catalog 6.2% of the total number of 51572 galaxies with apparent magnitudes of K s < 12.0 m , and angular diameters of a K > 30 ′′ .…”
Section: Isolated Galaxies Of the 2mig Catalogmentioning
confidence: 99%